Effects of malaria parasite density on blood cell parameters - Manas Kotepui (2018)
© 2015 Kotepui et al. Changes in blood cell parameters are already a well-known feature of malarial infections. To add to this information, the objective of this study was to investigate the varying effects that different levels of parasite density have on blood cell parameters. Patients diagnosed with malaria at Phobphra Hospital, Tak Province, Thailand between January 1 st 2009 and January 1 st 2012 were recruited as subjects for data collection. Blood cell parameters of 2,024 malaria-infected patients were evaluated and statistically analyzed. Neutrophil and platelet counts were significantly higher, however, RBC count was significantly lower in patients with P. falciparum infection compared to those with P. vivax infection (p < 0.0001). Leukocyte counts were also significantly higher in patients with high parasitemia compared to those with low and moderate parasitemia. In terms of differential leukocyte count, neutrophil count was significantly higher in patients with high parasitemia compared to those with low and moderate parasitemia (p < 0.0001). On the other hand, both lymphocyte and monocyte counts were significantly lower in patients with high parasitemia (p < 0.0001). RBC count and Hb concentration, as well as platelet count were also significantly reduced (p < 0.05) and (p < 0.0001), respectively. To summarize, patients infected with different malaria parasites exhibited important distinctive hematological parameters, with neutrophil and eosinophil counts being the two hematological parameters most affected. In addition, patients infected with different malarial densities also exhibited important changes in leukocyte count, platelet count and hemoglobin concentration during the infection. These findings offer the opportunity to recognize and diagnose malaria related anemia, help support the treatment thereof, as well as relieve symptoms of severe malaria in endemic regions.